Different effects of ozone and aqueous ammonia in a combined pretreatment method on rice straw and dairy manure fiber for enhancing biomethane production. (June 2019) - Ai, Ping; Zhang, Xiuzhi; Dinamarca, Carlos; Elsayed, Mahdy; Yu, Liang; Xi, Jiang; Mei, Zili
Highlights: Combined ozone and soaking in aqueous ammonia pretreatment processes were investigated. SAA time had a major function for pretreatment of rice straw via the OSAA pretreatment. Ozone time was more important than SAA for manure fiber via the OSAA process. Pretreatment parameters optimizing depends on the difference of substrates character. Abstract: Low digestibility of lignocellulosic feedstock is the most important limitation for biogas production. The synergistic effects of ozone and aqueous ammonia (OSAA) on different types of lignocelluloses including rice straw and dairy manure fiber were investigated. OSAA significantly increased biogas production of rice straw by 114.2%–172.8% when compared with using ozonation alone, while increased by 6.2%–8.8% with manure fiber. OSAA pretreatment increased biogas production of manure fiber by 55.3%–103.6% when compared with soaking aqueous ammonia (SAA) alone, while by 28.8%–39.9% with rice straw. The specific effects of pretreatment time on anaerobic digestion of manure fiber differed noticeably from those on rice straw. Ozonation time had a major function for pretreatment of manure fiber via the OSAA process, but SAA pretreatment time was more important than that for rice straw.